Versatile synthesis of α-fused BODIPY displaying intense absorption in the NIR region and high electron affinity. Issue 37 (4th September 2018) - Huaulmé, Quentin; Sutter, Alexandra; Fall, Sadiara; Jacquemin, Denis; Lévêque, Patrick; Retailleau, Pascal; Ulrich, Gilles; Leclerc, Nicolas
Abstract : A straightforward, highly regioselective and versatile chemical route allows the synthesis of α-fused boron dipyrromethene regioisomers. Abstract : We report the design and highly efficient and versatile synthesis of four isomers of α-fused boron dipyrromethene (BODIPY). Structure–property relationships have been established through photophysical and electrochemical properties analysis as well as first-principles calculations. A comparative study of their charge transport properties has been carried out in Organic Field Effect Transistor (OFET) devices, and this allowed the identification of a high mobility material (10 −2 cm 2 V −1 s −1 ) displaying balanced ambipolar behavior.